The Cone Structure Theorem - Batista, Erica Boizan; Costa, João Carlos Ferreira [UNESP]; Nuño-Ballesteros, Juan José (My University, 2021)
We consider the topological classification of finitely determined map germs f: (Rn, 0) → (Rp, 0) with f-1(0) = {0}. Associated with f we have a link diagram, which is well defined up to topological equivalence. We prove that f is topologically A-equivalent to the generalized cone of its link diagram.